2017
DOI: 10.1002/jcp.26118
|View full text |Cite
|
Sign up to set email alerts
|

β‐asarone inhibited cell growth and promoted autophagy via P53/Bcl‐2/Bclin‐1 and P53/AMPK/mTOR pathways in Human Glioma U251 cells

Abstract: Glioma is the most common type of primary brain tumor and has an undesirable prognosis. Autophagy plays an important role in cancer therapy, but it is effect is still not definite. P53 is an important tumor suppressor gene and protein that is closely to autophagy. Our aim was to study the effect of β-asarone on inhibiting cell proliferation in human glioma U251 cells and to detect the effect of the inhibition on autophagy through the P53 signal pathway. For cell growth, the cells were divided into four groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…37,38 Furthermore, a number of natural compounds have been found to modulate autophagy via this signaling pathway. 40 Consistently, we demonstrated that activation of the AMPK/mTOR signaling pathway was involved in XAG mediated induction of autophagy, as well as its antimetastatic and anti-EMT effects. 39 In human Glioma U251 cells, β-asarone induced autophagic cell death through activation of the P53/Bcl-2/ Beclin-1 and P53/AMPK/mTOR pathways.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…37,38 Furthermore, a number of natural compounds have been found to modulate autophagy via this signaling pathway. 40 Consistently, we demonstrated that activation of the AMPK/mTOR signaling pathway was involved in XAG mediated induction of autophagy, as well as its antimetastatic and anti-EMT effects. 39 In human Glioma U251 cells, β-asarone induced autophagic cell death through activation of the P53/Bcl-2/ Beclin-1 and P53/AMPK/mTOR pathways.…”
Section: Discussionsupporting
confidence: 63%
“…39 In human Glioma U251 cells, β-asarone induced autophagic cell death through activation of the P53/Bcl-2/ Beclin-1 and P53/AMPK/mTOR pathways. 40 Consistently, we demonstrated that activation of the AMPK/mTOR signaling pathway was involved in XAG mediated induction of autophagy, as well as its antimetastatic and anti-EMT effects. XAG significantly increased p-AMPK level in a dose-dependent manner and simultaneously decreased p-mTOR expression.…”
Section: Discussionsupporting
confidence: 63%
“…p53 is a major tumor suppressor gene that acts an important part in boosting apoptosis of cancer cells . In addition, research has shown that p53 can both promote apoptosis and inhibit apoptosis, and is a double‐face transcription factor .…”
Section: Discussionmentioning
confidence: 99%
“…Association of the expression level of miR-374a with clinicopathological factors of glioma. it was reported that the mTOR pathway is a crucial signaling pathway involved in the development of glioma (38). In addition, four hub genes, CCND1, SP1, CDK6 and CDK4, were identified from the PPI of predicted target genes of miR-374a, which may be directly or indirectly involved in the development of glioma.…”
Section: Discussionmentioning
confidence: 99%